Street tree composition, distribution and urban residents' perceptions within and between Eastern Cape towns - Gwedla, Nanamhla (Rhodes University, Faculty of Science, Department of Environmental Science, 2016)
Promoting urban sustainability is vital in the face of rapid human and urban population growth. A core tenet of urban sustainability, urban forestry, is poised to "go global" with the intent of mitigating the negative environmental and social effects of urbanisation through green infrastructure, spaces and trees. Amongst these, the planting of street trees has become a major strategy. The public functions of street trees as demonstrated through the provision of ecosystem services are highly dependent on the structure, composition and diversity of tree species within the urban forest. The bulk of available literature on the composition, diversity and perceptions of residents regarding street trees has largely focused on the developed world, while the few in the developing world have been conducted at only one or two sites. The aim of this study was to investigate the composition, diversity and density of urban street trees in relation to the perceptions of local residents and horticulturists, across a range of ecological and social contexts. To do this, the species composition, diversity and dominance of street trees planted in 10 randomly selected Eastern Cape towns was assessed. Within each town ten replicate 200 m transects were located in three different suburbs. Perceptions and appreciation of street trees were assessed by 1 200 household questionnaires, as well as key informant interviews with personnel responsible for street tree planting and maintenance. Sixty-nine out of 300 sampled transects had street trees, with 888 trees enumerated, spanning ninety-seven species. Alien tree species accounted for 71 % of all the enumerated trees while indigenous trees species accounted for 12 %. The non-former homeland towns had a significantly higher (5.8Â±1.6 trees) mean street tree density per transect than the former homeland towns (0.6Â±03). There were no significant relationships between street tree density or richness to mean annual rainfall or the background biome in which the town was situated. However, density strongly was related to size of the town. RDP and township suburbs had fewer street trees and low species richness relative to the affluent suburbs. In selecting street trees, root system of the prospective tree, the eventual size or shape of the species, whether an alien or indigenous species, and the species' adaptability to the climate of the respective town are considered before planting. The biggest identified threats to street trees were the deliberate vandalism of trees by people and animals, and lack of education and awareness regarding the importance of street trees among urban residents and municipal officials. More than half of the respondents prefer that trees be planted both on the street and in their yards while a few do not want trees at all. The majority of respondents with this preference do so because they want shade and abundant fruit, and to have beautiful yards and streets. Those who do not want trees at all do so because they just do not like trees, there is no space for trees, or they fear that criminals hide behind trees. The presence of trees in peoples' yards correlated with a positive preference for trees in the street. The majority of respondents were neither satisfied with the general appearance of their street nor with the number of trees on their street. Residents from the RDP suburbs were the least satisfied with both the appearance and number of trees on their streets, while those from the affluent suburbs were the most satisfied. Street trees were seen as greatly important to have by the majority of people. The more educated people were more appreciative of the importance of street trees. Local municipalities were identified by the majority of respondents as the stakeholders responsible for the planting and maintenance of street trees, although a considerable proportion of respondents reported a willingness to volunteer to help plant and maintain trees on their streets. Municipalities were seen as doing very little to provide and maintain trees in the various suburbs by the majority of respondents. The majority of respondents also reported that they had never been consulted about tree planting activities in their suburbs before, and would like to have been consulted.
Keywords: Urbanization -- South Africa -- Eastern Cape; Urban ecology (Sociology) -- South Africa -- Eastern Cape; Tree planting -- South Africa -- Eastern Cape; Trees in cities -- Environmental aspects -- South Africa -- Eastern Cape; Urban forestry -- Law and legislation -- South Africa -- Eastern Cape; Low-income housing -- South Africa -- Eastern Cape